Expert Experiences in Anonymizing Personal Data and Its Use as Open Data: Qualitative Insights - Norbert Lichtenauer; Johann Guggumos; Matthias Kampmann; Juliane Kis; Florian Laumer; Elena März; Florian Wahl; Sebastian Wilhelm (Data)
Introduction: The effective and meaningful use of anonymized personal data, including open data, is globally significant across various sectors. Enhancing data utilization aims to generate substantial societal benefits and added value through innovations, products, and services. However, several legal, ethical, and technical challenges currently hinder the development and broader adoption of open data. Furthermore, the availability of technical support tools with high usability is especially desirable to facilitate the anonymization process effectively. Methods: As part of the EAsyAnon research project, preliminary insights were gathered through a scoping review that identified factors promoting or impeding the anonymization and use of personal data. Based on these findings, a structured interview guide was developed. Following a pretest, 19 interviews were conducted with diverse stakeholders from healthcare institutions, research organizations, public authorities, and private companies. The collected data were analyzed using Kuckartz’s structural content analysis methodology, supported by qualitative analysis software. Results: The content analysis yielded five overarching categories and 21 subcategories. These encompassed stakeholder experiences related to anonymization and open data processes, the various types and formats of personal data, identified barriers and enabling factors, support services, and the ethical and legal considerations associated with anonymization. Discussion: The findings highlight significant uncertainty among stakeholders regarding the anonymization of personal data. Although the importance and potential applications of open data for innovation and continuous improvement are widely acknowledged and supported, numerous challenges persist at both the macro and micro levels. The results emphasize a clear need for targeted support measures to address these challenges effectively.